Enrichment of fishburgers with proteins from surimi washing wate - de OLIVEIRA, Dayse Lícia [UNESP]; Grassi, Thiago Luís Magnani [UNESP]; Bassani, Juliana Sedlacek [UNESP]; Diniz, Juliana Campos Pereira [UNESP]; Paiva, Natália Mingues [UNESP]; Ponsano, Elisa Helena Giglio [UNESP] (FapUNIFESP (SciELO), 2020)
The proteins recovered by ultrafiltration (UF) represent a co-product of fish industrialization and can be used as a proteiingredient in the fortification of food formulations. The objective of this study was to evaluate the quality of surimi fishburgeelaborated with the proteins recovered by UF from the wastewater generated in the production of surimi. The water generated ithe washing operations of trims of farmed tilapia (Oreochromis niloticus) were filtered in a 30 kDa polyethersulfone membranThe recovered proteins were dehydrated in spray dryer and added at 5 and 10% into fishburgers made with tilapia surimThe fishburgers were evaluated for proximal composition, cooking yield, sensory parameters and acceptability. The incorporatioof proteins into the fishburgers improved the sensory aspects of the final product and provided greater acceptability whilmaintaining the same manufacturing yield. The addition of 10% of the recovered proteins increased the nutritional value osurimi fishburgers. Practical Application: The recovery of proteins from surimi wastewaters reduces organic matter, makes the production procmore profitable and less aggressive to environment and, in addition, provides a protein-rich ingredient that may find use food industry. The use of this protein concentrate in food products like surimi increases nutritional quality and productivand so may reach consumers and producers demands.
Keywords: Co-product; Sensory analysi; Tilapia; Ultrafiltration